Carbon chain elongation microorganism stimulates caproate production from ethanol and acetate under applied voltage regulation - Li, Jing; Luo, Xing; Liu, He; Zhang, Xuedong; Tan, Hao; Xiong, Xiaolong (Frontiers in Microbiology, 2025)
Carbon chain elongation has been an innovative process for the synthesis of medium-chain fatty acids (MCFAs). Among them, caproate is a vital multi-functional one. To enhance the synthesis efficiency of caproate, the growth conditions of carbon chain elongation microorganisms need to optimize to develop an ideal niche, ultimately enhancing the production of caproate. In this study, the microbial enrichment of carbon chain elongation was obtained and the optimal system of carbon chain elongation was constructed. The optimal condition for carbon chain elongation was achieved at a pH of 7.00, an ethanol/acetic acid carbon molar ratio of 4:1, and a voltage of 0.7 V. The result showed that the concentration of caproate in the optimal group increased by 83.09% in comparison to the control group. Subsequently, compared with the initial microbial community structure, the relative abundance of microorganisms changed greatly in the optimal system, including Clostridium_sensu_stricto_12, Christensenellaceae_R-7_group, Anaerofilum, Clostridium_sensu_stricto_7, and Intestinimonas. Additionally, functional prediction analysis revealed that the optimal system enhanced amino acid metabolism (alanine, aspartate, and glutamate), carbon metabolism (CoA biosynthesis), and energy metabolism by 33.66, 30.42, and 17.05%, respectively. Besides, both the fatty acid biosynthesis (FAB) and reverse β oxidation (RBO) pathways were enhanced in optimal system. This study elucidates a novel mechanistic insight into the efficient microbial synthesis of caproate through carbon chain elongation pathways, demonstrating how applied voltage regulation can significantly enhance the bioproduction of MCFAs from simple substrates such as ethanol and acetate. Furthermore, this work presents a sustainable and energy-efficient strategy for caproate production, reducing reliance on fossil-derived precursors.